The Application of Interactive Music within a Video Game Score: An Analysis of the Development and Use of Interactive Music in Video Games - Honas, Matthew (My University, 2016)
Video games have had a short but exciting history. Throughout the years, the musical contribution to video games has progressively improved and become an essential part of the video game experience. Music changed quickly to compensate for hardware limitations and to avoid repetition. With the interactivity in video game music being a new concept, many people disagree about what terms to use when defining video game music and the different techniques. Composers also had to learn to employ a variety of techniques and strategies to achieve interactivity in games and to further immerse the player and create a more believable world. Because of the complexity of interactive music, composers also need to work with game designers to implement an intelligent music system. Overall, the further player immersion into the video game world shows the importance of the integration of interactive music.